Implementation of Thematic Bureaucratic Reform: Level of Understanding and Realization in Local Government - Suhartono Winoto; Laily Akbariah; Lailla Dwi Yulitasari; Catherine Eugene Natasha; Ima Kumalasari; Ting Poh Yin (CV. Austronesia Akademika, 2024)
Thematic bureaucratic reform is a program initiated by the Ministry of State Apparatus Empowerment and Bureaucratic Reform (Kemenpan-RB) to accelerate the improvement of efficiency and accountability of public services in Indonesia. This research aims to elaborate the level of understanding of the State Civil Apparatus (ASN) and the realization of the implementation of thematic bureaucratic reform at the local government level. A descriptive qualitative method is used in this study. The data was obtained based on an in-depth interview technique with a resource person from one of the employees in the City Government who has credibility in the preparation of bureaucratic reform. The results obtained in this study show that thematic bureaucratic reform is indeed the right step in the acceleration program to improve public services. In addition, there is a focus on the theme of bureaucratic reform which is divided into 4 (four) categories, namely poverty alleviation, increasing investment, digitizing government administration, and increasing the use of domestic products. However, in reality, in the field, there are still several obstacles in the preparation of the thematic bureaucratic reform roadmap, where the main obstacle is the lack of understanding of ASN in the preparation of the thematic bureaucratic reform roadmap. The hope in the future is that there will be a forum or in-depth socialization or technical guidance from the Ministry that can help overcome ASN problems related to the technical preparation of thematic bureaucratic reform roadmaps and integration with existing programs in local governments.